2006
DOI: 10.1016/j.jasms.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-phospholipid cross-linking reactions: Identification of leucine enkephalin-alka(e)nal-glycerophosphatidylcholine adducts by tandem mass spectrometry

Abstract: The covalent interactions between peptides and lipid oxidation products, with formation of Schiff and Michael adducts, are known to occur during free radical oxidative damage. In this study, leucine-enkephalin-glycerophosphatidylcholine alka(e)nal adducts were analyzed by electrospray tandem mass spectrometry (MS/MS). Upon collision-induced dissociation of the Leucine enkephalin-2-(9-oxo-nonanoyl)-1-palmitoyl-3-glycerophosphatidylcholine, an alkanal Schiff adduct observed at m/z 1187.7, the main product ions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Reis et al . investigated in vitro the reactivity of 1‐palmitoyl‐2‐(9‐oxo‐nonanoyl)‐GPC with leucine enkephalin and found that the terminal amino group can form a Schiff base (+631.5 u) with PC‐bound aldehyde . In our previous study, we reported lysine to form Schiff base with 1‐palmitoyl‐2‐(9‐hydroxy‐12‐oxo‐dodecenoyl)‐GPC (+687.5 u) and Michael adducts with 1‐palmitoyl‐2‐(9‐keto‐12‐oxo‐dodecedienoyl)‐GPC (+703.5 u) and 1‐palmitoyl‐2‐(9‐keto‐10,12‐octadecadienoyl)‐GPC (+771.5 u) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reis et al . investigated in vitro the reactivity of 1‐palmitoyl‐2‐(9‐oxo‐nonanoyl)‐GPC with leucine enkephalin and found that the terminal amino group can form a Schiff base (+631.5 u) with PC‐bound aldehyde . In our previous study, we reported lysine to form Schiff base with 1‐palmitoyl‐2‐(9‐hydroxy‐12‐oxo‐dodecenoyl)‐GPC (+687.5 u) and Michael adducts with 1‐palmitoyl‐2‐(9‐keto‐12‐oxo‐dodecedienoyl)‐GPC (+703.5 u) and 1‐palmitoyl‐2‐(9‐keto‐10,12‐octadecadienoyl)‐GPC (+771.5 u) .…”
Section: Discussionmentioning
confidence: 99%
“…While alkanals can modify only primary amines through Schiff base formation, alkenals, alkadienals and hydroxy‐alkenals can additionally form Michael adducts with histidine imidazole and cysteine thiol . Protein modifications resulting from low molecular weight carbonyls were intensively studied during the last decade, while peptide and protein modifications by lipid‐bound carbonyls were only sporadically reported …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonylated phospholipids (PL‐oxoLPP), that is, oxidized polyunsaturated fatty acids‐PL esters, are the dominant species of modified PL in vivo capable to modify nucleophilic substrates. In contrast to aliphatic oxoLPP, however, protein modifications resulting from lipid‐bound carbonyls have been rarely reported . The detection of protein‐oxoLPP in complex biological matrices relies on either specific immunoassays or sensitive mass spectrometry techniques, though the analysis of PL‐oxoLPP–protein adducts is challenged in reversed phase chromatography‐MS by the physicochemical properties, relatively low quantities in biological samples, and multiple positional isomers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phospholipids, present in cell membranes, low-density lipoproteins (LDL), cholesterol and triglycerides [2], playing an important role in membrane structure, metabolism and signal transduction [3], are also major targets of free radicals and have not been so extensively studied. Nonetheless, from the works published it has been inferred that the structural changes caused by radical peroxidation in phospholipids, such as phosphatidylcholines, affect the physical properties of the membrane bilayers [4,5] which are reflected in membrane integrity [6]; and are also responsible for covalent cross-linking between oxidised lipid moieties and proteins [7,8] leading to inactivation of membrane proteins and/or receptors [9]. In some cases, oxidised phospholipids show biological activity similar to platelet aggregating factors (PAF) [10], or may act as promoters in the expression of several genes, as proposed in the tumorogenesis of breast cancer cells [11].…”
Section: Introductionmentioning
confidence: 99%